Death by Degrees: Taking a Feminist Hard Look at the 2° Climate Policy - Seager, Joni (Kvinder, Køn & Forskning, 2009)
International policy-makers are forging a consensus that a 2° rise in global temperature represents an acceptable level of danger to the planet. This is not based on climate science. This article explores how feminist analysis and perspectives on climate change can help to reveal the gendered political and ideological underpinnings of this approach to climate change.